Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.3855/jidc.245
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C virus co-infection in Nigerian patients with HIV infection

Abstract: Introduction: We set out to determine the seroprevalence of hepatitis B and hepatitis C viruses among human immunodeficiency virus infected individuals and its impact on pattern of presentation. Methodology: A serological study for hepatitis B and hepatitis C viruses was performed on 260 HIV-positive individuals. These patients were tested for the presence of hepatitis B surface antigen and anti-hepatitis C virus (HCV) antibody. Results: Thirty (11.5%) patients tested positive for hepatitis B surface antigen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
49
6
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 16 publications
(25 reference statements)
23
49
6
3
Order By: Relevance
“…This is similar to the findings in an HIV treatment center in Enugu, Nigeria [29,30]. Also in other HIV treatment centers in Nigeria [31][32][33]. This may be due to the higher prevalence of HIV among females in Nigeria than males, as reported in the 2012 National HIV and AIDS and Reproductive Health survey (NARHS 2012) conducted by the Federal Ministry of Health [34].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This is similar to the findings in an HIV treatment center in Enugu, Nigeria [29,30]. Also in other HIV treatment centers in Nigeria [31][32][33]. This may be due to the higher prevalence of HIV among females in Nigeria than males, as reported in the 2012 National HIV and AIDS and Reproductive Health survey (NARHS 2012) conducted by the Federal Ministry of Health [34].…”
Section: Discussionsupporting
confidence: 78%
“…Majority of the respondents in this study were married (56.2%) this is similar to the findings of a study done in Enugu [30] and a study done at Ibadan [31]. This is dissimilar to the 2010 National HIV Seroprevalence sentinel survey which reported that the prevalence of HIV was higher among the single women than the married [35].…”
Section: Discussionsupporting
confidence: 54%
“…24 Studies from Nigeria and Tanzania in outpatient HIV clinics showed widely varying rates of 2.3% and 18.1%, respectively. 11,12 Additionally, a Botswana study at a major urban hospital showed a HCV coinfection rate of 0%. 17 The Botswana-Baylor Children's Clinical Center of Excellence (BCOE) is a national HIV/AIDS care and treatment facility that provides services in Gaborone, Botswana for HIV-infected children from around the country.…”
Section: Introductionmentioning
confidence: 99%
“…The factors associated with co-infection in this study were history of blood transfusion, lack of immunization against hepatitis B, and duration of ART lower than five years. Other authors have also identified blood transfusion as associated with co-infection in Benin and Nigeria [22,23]. We can assume with the results in Table 5 that HIV infected children with history of blood transfusion are running 2.64 times risk of hepatitis.…”
Section: Discussionmentioning
confidence: 64%